Assessing long‐term impacts of cover crops on soil organic carbon in the central US Midwestern agroecosystems. Issue 9 (28th February 2023) - Qin, Ziqi; Guan, Kaiyu; Zhou, Wang; Peng, Bin; Tang, Jinyun; Jin, Zhenong; Grant, Robert; Hu, Tongxi; Villamil, María B.; DeLucia, Evan; Margenot, Andrew J.; Umakant, Mishra; et al.
Abstract: Cover crops have been reported as one of the most effective practices to increase soil organic carbon (SOC) for agroecosystems. Impacts of cover crops on SOC change vary depending on soil properties, climate, and management practices, but it remains unclear how these control factors affect SOC benefits from cover crops, as well as which management practices can maximize SOC benefits. To address these questions, we used an advanced process‐based agroecosystem model, ecosys, to assess the impacts of winter cover cropping on SOC accumulation under different environmental and management conditions. We aimed to answer the following questions: (1) To what extent do cover crops benefit SOC accumulation, and how do SOC benefits from cover crops vary with different factors (i.e., initial soil properties, cover crop types, climate during the cover crop growth period, and cover crop planting and terminating time)? (2) How can we enhance SOC benefits from cover crops under different cover crop management options? Specifically, we first calibrated and validated the ecosys model at two long‐term field experiment sites with SOC measurements in Illinois. We then applied the ecosys model to six cover crop field experiment sites spanning across Illinois to assess the impacts of different factors on SOC accumulation. Our modeling results revealed the following findings: (1) Growing cover crops can bring SOC benefits by 0.33 ± 0.06 MgC ha −1  year −1 in six cover crop field experiment sites across Illinois, and the SOC benefits are species specific to legume and non‐legume cover crops. (2) Initial SOC stocks and clay contents had overall small influences on SOC benefits from cover crops. During the cover crop growth period (i.e., winter and spring in the US Midwest), high temperature increased SOC benefits from cover crops, while the impacts from larger precipitation on SOC benefits varied field by field. (3) The SOC benefits from cover crops can be maximized by optimizing cover crop management practices (e.g., selecting cover crop types and controlling cover crop growth period) for the US Midwestern maize–soybean rotation system. Finally, we discussed the economic and policy implications of adopting cover crops in the US Midwest, including that current economic incentives to grow cover crops may not be sufficient to cover costs. This study systematically assessed cover crop impacts for SOC change in the US Midwest context, while also demonstrating that the ecosys model, with rigorous validation using field experiment data, can be an effective tool to guide the adaptive management of cover crops and quantify SOC benefits from cover crops. The study thus provides practical tools and insights for practitioners and policy‐makers to design cover crop related government agricultural policies and incentive programs for farmers and agri‐food related industries. Abstract : In this study, we used the process‐based ecosys model to quantify SOC benefits from cover crops in maize‐soybean rotations in the central U.S. Midwestern agroecosystems. Our study revealed that different factors control SOC change and SOC benefits from cover crops, including initial soil properties, cover crop types, climate during the cover crop growth period, and cover crop planting and terminating time.